# Arithmetic progression if the sum of first p terms of an a.p is equal to the sum of first q terms then show that the sum of its first (p+q) terms is zero where pis not equal to q

2
by kevalsavla160

2014-11-13T12:14:07+05:30

### This Is a Certified Answer

Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.
Let the first term = a
common difference = d
Sum of first n terms is S(n) = (n/2) [ 2a + (n-1) d ]

S(p) = S(q)
⇒ (p/2) [ 2a + (p-1)d ] = (q/2) [ 2a + (q-1)d ]
⇒ 2ap + (p²-p)d = 2aq + (q²-q)d
⇒ 2ap + (p²-p)d - 2aq - (q²-q)d =0
⇒ 2ap + p²d - pd - 2aq - q²d - qd =0
⇒ 2a(p-q) + (p²-q²)d - (p-q)d = 0
⇒ 2a(p-q) + [ (p²-q²) - (p-q) ]d = 0
⇒ 2a(p-q) + [ (p-q)(p+q) - (p-q) ]d = 0
⇒ 2a(p-q) + (p-q)[ (p+q) - 1]d = 0
⇒ (p-q) [ 2a + (p+q-1)d ] = 0
⇒ 2a + ( p+q-1)d = 0            (as p and q are not equal, p-q is not equal to 0)

Sum of (p+q) terms is

S(p+q) = [ (p+q)/2 ] [ 2a + (p+q-1)d ]
= [ (p+q)/2 ] × 0
= 0 (proved)
• Brainly User
2014-11-13T12:45:16+05:30
S(p) = S(q)
p/2 [2a + (p-1) d] = q/2 [2a + (q - 1) d]
2ap + (p - 1)dp =  2aq + (q - 1)dq
2ap - 2aq + p²d - pd - q²d + qd = 0
2a(p - q) + d(p² - q²) - d(p - q) = 0
(p - q) [2a + d(p + q) - d] = 0
[2a + d(p + q) - d] = 0
[2a + d(p + q - 1)] = 0 ...............(1)

S(p+q) = (p+q)/2 [2a + d(p + q - 1)]
= (p+q)/2 [0]   .........[from (1) ]
= 0